The Digital Transformation of Healthcare: AI Hospital Management vs. Traditional Systems - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The Digital Transformation of Healthcare: AI Hospital Management vs. Traditional Systems The healthcare industry is undergoing a profound transformation...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Machine Learning; Medical Ethics